Dukungan Sosial terhadap Burnout Syndrome pada Perawat dalam Layanan Pasien COVID-19 - Dinda Nur Fajri Hidayati Bunga; Rotua Suriany Simamora; Kiki Deniati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the relationship between social support and burnout syndrome in nurses serving COVID-19 patients. This research method uses a quantitative methodology with an analytic design. This study found that most respondents with good social support were 30 (76.9%), and mild burnout syndrome 29 (74.4%). The results of statistical analysis obtained a p-value of 0.000. In conclusion, there is a relationship between social support and burnout syndrome in nurses serving COVID-19 patients Keywords: Workload, COVID-19, Social Support